Graphene-based antenna: enabling fat-intrabody communication at 2.45 GHz ISM band - Subramaniam, Sree Aran; Asan, Noor Badariah; Asli, Muhammad Azwan Faiz; Augustine, Robin (2023)
This paper describes a graphene-based antenna designed for fat intrabody communication at 2.45 GHz. The antenna utilizes graphene’s unique properties, such as conductivity and compatibility with biological systems. It is a planar meandered inverted F antenna (MIFA) printed on a silicone substrate. The antenna’s efficacy is evaluated within a three-layered tissue structure and different inter-antenna distances. The results show adequate impedance matching within fat tissue, resonance at 2.45 GHz, and a competent transmission coefficient. The study explores the impact of three layered tissue separation and depth on antenna propagation performance between the transmission coefficient and distance. The graphene-based antenna offers promising potential for effective intrabody communication in biomedical applications.